Characteristics of carcinogenic HPV genotypes in North China Plain and the association with cervical lesions. Issue 37 (September 2019) - Liu, Lihua; Wang, Dexue; Dong, Haixin; Jin, Chengqiang; Jiang, Liqing; Song, Hui; Jin, Chao; Wang, Tong; Shi, Cuiming; Yang, Linqing; Wang, Yunfei
Abstract : Abstract: Human papillomavirus (HPV) infection is a crucial health problem and caused substantial malignancy diseases among female worldwide. We aim to investigate the distribution of HPV subtype and the status of cervical cancer and precancerous lesions caused by HPV infection in North China Plain population. A total of 61, 870 samples of outpatients and inpatients from January 2015 to May 2017 at the Affiliated Hospital of Jining Medical University were collected. All of the samples were tested by rapid flow-through hybridization HPV genotyping. Approximately 17, 280 of the cases tested positive for HPV, indicating an infection rate of 27.9%. Approximately 7009 cases were compared to the results of cytological diagnosis. The top five HPV genotypes were HPV-16 (4.5%), HPV-52 (2.9%), HPV-58 (2.8%), HPV-53 (1.9%), and HPV-81 (1.9%). The youngest age group (age < 20 years) showed the highest infection rate (59.9%), and then decreased with age. As the degree of cervical lesions worsened gradually, the rate of high-risk HPV infection increased, such as 24.3% (322/1324) in the Cervicitis, 31.30% (560/1785) in the CINI, 54.1% (568/1050) in the CINII, 80.1% (693/865) in the CIN III, and 99.5% (428/430) in the cervical cancer group. These findings were significantly different from the 9.7% (155/1555) observed in the normal medical examination group ( P < .05). This is the first study to demonstrate the characteristics of HPV and the association with cervical lesions in North China Plain population.